Improvement of gait by chronic, high doses of methylphenidate in patients with advanced Parkinson's disease. Issue 5 (10th November 2006) - Devos, D; Krystkowiak, P; Clement, F; Dujardin, K; Cottencin, O; Waucquier, N; Ajebbar, K; Thielemans, B; Kroumova, M; Duhamel, A; Destée, A; Bordet, R; et al.
Abstract : Background: Therapeutic management of gait disorders in patients with advanced Parkinson's disease (PD) can sometimes be disappointing, since dopaminergic drug treatments and subthalamic nucleus (STN) stimulation are more effective for limb-related parkinsonian signs than for gait disorders. Gait disorders could also be partly related to norepinephrine system impairment, and the pharmacological modulation of both dopamine and norepinephrine pathways could potentially improve the symptomatology. Aim: To assess the clinical value of chronic, high doses of methylphenidate (MPD) in patients with PD having gait disorders, despite their use of optimal dopaminergic doses and STN stimulation parameters. Methods: Efficacy was blindly assessed on video for 17 patients in the absence of l -dopa and again after acute administration of the drug, both before and after a 3-month course of MPD, using a Stand–Walk–Sit (SWS) Test, the Tinetti Scale, the Unified Parkinson's Disease Rating Scale (UPDRS) part III score and the Dyskinesia Rating Scale. Results: An improvement was observed in the number of steps and time in the SWS Test, the number of freezing episodes, the Tinetti Scale score and the UPDRS part III score in the absence of l -dopa after 3 months of taking MPD. The l -dopa-induced improvement in these various scores was also stronger after the 3-month course of MPD than before. The Epworth Sleepiness Scale score fell dramatically in all patients. No significant induction of adverse effects was found. Interpretation: Chronic, high doses of MPD improved gait and motor symptoms in the absence of l -dopa and increased the intensity of response of these symptoms to l -dopa in a population with advanced PD.